Discriminative validity of the Scoliosis Research Society 22 questionnaire among five curve-severity subgroups of adolescents with idiopathic scoliosis - Berliner, Jonathan L.; Verma, Kushagra; Lonner, Baron S.; Penn, Phedra U.; Bharucha, Neil J. (The spine journal, 2013)
Previous studies of the Scoliosis Research Society (SRS) 22 discriminative validity have lacked sufficiently matched study groups and were limited to a comparison with three or fewer subgroups of disease severity. To evaluate the discriminative validity of SRS-22 by assessing the questionnaire's ability to discriminate among five groups of pretreatment adolescent idiopathic scoliosis (AIS) patients with increasing curve severity. Retrospective review of prospectively administered surveys. Two hundred eighty-six SRS-22 questionnaires were issued to two AIS pretreatment patient populations: 67 nonoperative and 219 preoperative. Study subjects were separated into five subgroups depending on the major Cobb angle (nonoperative 0°–19° and 20°–40° and preoperative 41°–50°, 51°–60°, and >60°). Each group (n=31) was matched for age (within 1 year) and sex (23 females and 8 males), resulting in a total of 155 study subjects. Analysis of variance was used to determine statistically significant differences (p<.05) between the five subgroups' domains and total scores. Significant differences between study groups were found within two of the four domains (pain and image) and the total score. Both nonoperative groups (0°–19° and 20°–40°) demonstrated significantly less pain than the preoperative group (41°–50°) and significantly better self-image than all three preoperative groups. Both nonoperative groups' total scores were significantly higher than all three preoperative groups' scores, with the exception of the 20° to 40° subgroup versus the >60° subgroup. No significant differences were found between groups within the same planned treatment category. The SRS-22 questionnaire demonstrated good discriminative validity between small nonoperative curves and larger surgical curves within the pain, image, and total domains. However, SRS-22 lacked the ability to differentiate between small intervals of curve magnitude, suggesting a limitation to the questionnaire's discriminative capacity. The discriminative validity of the Scoliosis Research Society (SRS) 22 has not been clearly defined. Our analysis of 155 adolescent idiopathic scoliosis patients evaluates the instrument's discriminative validity among five age- and sex-matched curve-severity subgroups. The SRS-22 questionnaire lacked the ability to differentiate between small intervals of curve magnitude, suggesting a limit to the questionnaire's discriminative capacity.